2012
DOI: 10.1002/hep.24654
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Eight Diagnostic Algorithms for Liver Fibrosis in Hepatitis C

Abstract: The sequential algorithm for fibrosis evaluation (SAFE) and the Bordeaux algorithm (BA), which cross–check FibroTest with the aspartate aminotransferase–to–platelet ratio index (APRI) or FibroScan, are very accurate but provide only a binary diagnosis of significant fibrosis (SAFE or BA for Metavir F ≥ 2) or cirrhosis (SAFE or BA for F4). Therefore, in clinical practice, physicians have to apply the algorithm for F ≥ 2, and then, when needed, the algorithm for F4 (“successive algorithms”). We aimed to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 23 publications
1
85
0
2
Order By: Relevance
“…The non-invasive approaches include the evaluation of various laboratory parameters which are included in Fibrosure/Fibrotest, or in conjunction with liver stiffness evaluation by Fibroscan, which could obviate the need for liver biopsy with over 86.7% accuracy. 10 However, many medical centers still do not carry the Fibroscan or other liver stiffness measurement tools and are not able to conduct this testing with ease.…”
Section: Discussionmentioning
confidence: 99%
“…The non-invasive approaches include the evaluation of various laboratory parameters which are included in Fibrosure/Fibrotest, or in conjunction with liver stiffness evaluation by Fibroscan, which could obviate the need for liver biopsy with over 86.7% accuracy. 10 However, many medical centers still do not carry the Fibroscan or other liver stiffness measurement tools and are not able to conduct this testing with ease.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosztikus érzé-kenység növelhető, ha két független módszert kombinálnak, például TE-t együtt szérummarker-vizsgálattal [15,22]. Papastergiou és mtsai szerint a TE akár 90%-ban feleslegessé teheti a biopsziát.…”
Section: A Májbetegség Stádiummeghatározásaunclassified
“…Algorithms for combined use of serum markers and elastography have been proposed, with specific cut-off values being used in the decision trees. [3][4][5] However, a cut-off value for staging always involves a compromise between sensitivity and specificity. The use of Bayesian prediction to stage liver fibrosis involves calculating the stage based on elastographic or serum biomarker measures (see Appendix).…”
Section: Bayesian Prediction For Liver Fibrosis Staging: Combined Usementioning
confidence: 99%
“…On the other hand, BMSCs possess the ability to transdifferentiate into myofibroblasts that produce extracellular matrix (ECM) constituent and contribute to tissue repair. 3 One recent study demonstrated that acute liver failure triggered the activation of hepatic stellate cells and enhanced the formation of ECM, which reciprocally provide an optimal architecture for support of hepatocyte repopulation. 4 Among animals assigned to the intraportal transplantation group, an approximately and completely healthy liver structure was exhibited at weeks 3 and 5, respectively.…”
Section: Immediate Intraportal Transplantation Of Human Bone Marrow Mmentioning
confidence: 99%